Kosmologi dalam Tinjauan Failasuf Islam - Fuad Mahbub Siraj (ILMU USHULUDDIN, 2014)
One of the many important matters that is referred in the Qur’ān is a matter of the universe. The verses of Qur’ān invite people to observe and reflect on the creation of the universe, because in it there are signs of God’s existence and power. Cosmology is the theory about the origin of the universe. In Islam, this theory is one of the essential issues that have deep theological concequences and implications to the tawhīd. In order to formulate the process of the universe creation, the perspective of the Muslims was sorting into two extreme groups: traditionalists and rationalists. In the Islamic philosophy, in terms of the creation, the cosmology of al-Fārābī and Ibn Sīnā was influenced by the emanation of Plotinus’ philosophy and in terms of the structure is based on the concept of a geocentric Ptolomeus. While al-Ghazālī’s cosmology (representative of the traditionalist) based on the principle of the absolute will of God which is absolute. This study wants to reveal about the cosmology in the Islamic philosophers perspective as one of the cosmological mainstream which is speculative and revives the school of Aristotle, but not contrary to the principles of al-Qur’ān.